Sphingosine Kinase 1 Regulates Inflammation and Contributes to Acute Lung Injury in Pneumococcal Pneumonia via the Sphingosine-1-Phosphate Receptor 2 - Gutbier, Birgitt; Schönrock, Stefanie M; Ehrler, Carolin; Haberberger, Rainer; Dietert, Kristina; Gruber, Achim D; Kummer, Wolfgang; Michalick, Laura; Kuebler, Wolfgang M; Hocke, Andreas C; Szymanski, Kolja; Letsiou, Eleftheria; et al. (Critical care medicine, 2018)
Severe pneumonia may evoke acute lung injury, and sphingosine-1-phosphate is involved in the regulation of vascular permeability and immune responses. However, the role of sphingosine-1-phosphate and the sphingosine-1-phosphate producing sphingosine kinase 1 in pneumonia remains elusive. We examined the role of the sphingosine-1-phosphate system in regulating pulmonary vascular barrier function in bacterial pneumonia. Controlled, in vitro, ex vivo, and in vivo laboratory study. Female wild-type and SphK1-deficient mice, 8-10 weeks old. Human postmortem lung tissue, human blood-derived macrophages, and pulmonary microvascular endothelial cells. Wild-type and SphK1-deficient mice were infected with Streptococcus pneumoniae. Pulmonary sphingosine-1-phosphate levels, messenger RNA expression, and permeability as well as lung morphology were analyzed. Human blood-derived macrophages and human pulmonary microvascular endothelial cells were infected with S. pneumoniae. Transcellular electrical resistance of human pulmonary microvascular endothelial cell monolayers was examined. Further, permeability of murine isolated perfused lungs was determined following exposition to sphingosine-1-phosphate and pneumolysin. Following S. pneumoniae infection, murine pulmonary sphingosine-1-phosphate levels and sphingosine kinase 1 and sphingosine-1-phosphate receptor 2 expression were increased. Pneumonia-induced lung hyperpermeability was reduced in SphK1 mice compared with wild-type mice. Expression of sphingosine kinase 1 in macrophages recruited to inflamed lung areas in pneumonia was observed in murine and human lungs. S. pneumoniae induced the sphingosine kinase 1/sphingosine-1-phosphate system in blood-derived macrophages and enhanced sphingosine-1-phosphate receptor 2 expression in human pulmonary microvascular endothelial cell in vitro. In isolated mouse lungs, pneumolysin-induced hyperpermeability was dose dependently and synergistically increased by sphingosine-1-phosphate. This sphingosine-1-phosphate-induced increase was reduced by inhibition of sphingosine-1-phosphate receptor 2 or its downstream effector Rho-kinase. Our data suggest that targeting the sphingosine kinase 1-/sphingosine-1-phosphate-/sphingosine-1-phosphate receptor 2-signaling pathway in the lung may provide a novel therapeutic perspective in pneumococcal pneumonia for prevention of acute lung injury.